Psychotherapeutic Approaches to Sexual Problems : an Essential Guide for Mental Health Professionals. - Levine, Stephen B. (American Psychiatric Association Publishing, 2019)
The book aims to increase the comfort of both mental health trainees and advanced practitioners in assisting patients with their sexual concerns. The author provides a thoughtful discussion of the nature of love -- as an active, evolving process involving psychological intimacy, intense sexual interest, and commitment -- and shows how sexual problems create barriers to loving.